Brassinosteroid Applications Enhance the Tolerance to Abiotic Stresses, Production and Quality of Strawberry Fruits - Furio, Ramiro Nicolas; Salazar, Sergio Miguel; Mariotti Martinez, Jorge Alberto; Martinez Zamora, Martin Gustavo; Coll, Yamilet; Díaz Ricci, Juan Carlos (MDPI, 2022)
Brassinosteriods (BRs) have increasingly been used to improve the yields and quality of various crops. In this work we studied the effect of two brassinosteroids, BB16 and EP24, on the growth promotion of Fragaria ananassa plants under normal conditions or exposed to water or saline stress. The influence of both BRs on the plant development and fruit quality was evaluated when cultivated in semi-hydroponic conditions. A marked growth-promoting effect was observed with both compounds when plants were cultivated under normal irrigation conditions and under saline and water stresses. BB16 and EP24 yielded plants with a higher dry weight, root length and surface, a higher number and area of leaves, a higher total weight of fruits per plant, and a higher percentage of fruits of commercial quality. Additionally, a higher content of chlorophyll, number of leaves, and increased dry weight was detected in plants treated with both BRs and exposed to water and saline stresses. Finally, when evaluating the production and quality of fruits obtained under semi-hydroponic conditions, we observed that the pre-harvest treatment with both compounds induced a higher fruit production and better quality of fruits. These results suggest the potential of these compounds to achieve a more sustainable management of strawberry cultivation.